Physico-chemical properties of red tilapia (Oreochromis spp.) during surimi and kamaboko gel preparation - Seighalani, Fariba Zad Bagher; Bakar, Jamilah; Saari, Nazamid (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Physico-chemical properties of red tilapia mince during the preparation of surimi and kamaboko gel were evaluated to determine the potential of red tilapia as a source for surimi. Processing of red tilapia for surimi and kamaboko gel resulted in a significant lower Ca2+ ATPase activity, protein and fat than mincemeat. Thermograms of Differential Scanning Calorimetry (DSC) showed three peaks at 31.0, 54.5 and 72.0°C for the mince and only two peaks for surimi and kamaboko gel respectively. Enthalpies of myosin peaks in surimi and kamaboko gel were lower compared to the mincemeat, but there were no significant differences among the enthalpies (∆H) of their actin peaks. The highest maximum storage modulus (G’max) was obtained at 78.5°C for kamaboko gel which corresponded to 2420 Pa. The sodium dodecyl sulfate (SDS-PAGE) gel showed apparent intensity different in myosin (205 kDa) and no obvious differences for actin (43 kDa).